Work-time underemployment and financial hardship: class inequalities and recession in the UK. (April 2015) - Warren, Tracey
The economic crisis that led to recession in the UK in 2008–9 impacted in multiple ways on work and economic life. This article examines changes to the work-time of employees. The UK stood out for its recessionary expansion of work-time underemployment. Working in a job that provides 'too few' hours can have serious ramifications for the economic livelihood of workers. Working-class workers are central here. Drawing on analysis of large-scale survey data, the article identifies that workers in lower level occupations experienced the most substantial post-recessionary growth in the proportions working 'too few' hours. Did these work-time changes narrow or widen class inequalities in feelings of financial hardship? The article concludes that although middle-class workers also saw their financial positions damaged, this so-called 'first middle-class recession' did not erode class inequalities in financial hardship among UK workers.